EXPLORING THE COMPETENCY OF GROUND SERVICE STAFF: THE APPLICATION OF INTERDISCIPLINARY EDUCATION IN COLLEGE VIA THE DACUM ANALYSIS METHOD - Yang, Cheng Hua; Chou, Jun Tzu (PEOPLE: International Journal of Social Sciences, 2020)
This study explores the competency of airlines’ ground service staff and how to narrow the gap between academia and industry. Using the Developing A Curriculum (DACUM) method, which identifies and describes the competencies required for a job, observation of the workplace, and the opinion of experts, this study offers recommendations for the development of curriculums from both academic and industrial perspectives. The results show that the competency profile of airline ground service staff contains 8 duties, 129 tasks, and 101 competencies, including 31 items of knowledge, 34 items of skills, and 36 items of attitudes. It further shows that certain courses need to be included in interdisciplinary education. These include knowledge of the aviation industry, integration ability, an introduction to crime prevention, an understanding of the tourism industry, an understanding of business management, IT skills, legal knowledge, public relations, and some medical experience. These subjects should be applied to curriculum development in college.